Quechua religious songs in the Cemetery of Nueva Esperanza - Limachi Arévalo, Juan Edgar (2021)
In this paper we will make an approach to the religious songs in Quechua language, such as the Apu Yaya Jesus Christ and its variant found in the Cemetery of Nueva Esperanza, in the District of Villa Maria del Triunfo, located in the southern area of Lima. What are its variants and similarities in different contexts, taking as a reference the version used in the Cathedral of Cusco, where it has its roots at the end of the XVI century. Likewise, we will seek an approach to the particularities of the funeral chant Siwarcito (Aya taki), dedicated during the funerals in this cemetery by the bereaved in honor of their deceased loved ones. We will refer to previous studies by Montoya (2010), Durston (2010), Pilco Paz (2005), Mannheim and Firestone (2017). The work will be approached from a sociolinguistic point of view and with a qualitative analysis methodology.